Growth and quality of Basil (Ocimum basilicum L.) in soilless culture media as affected by light intensity - Julia Sahira Staman. (2012)
A study was conducted to determine the effects of light intensity, 100%, 50% and 30% sunlight on growth and quality of basil grown in soilless culture at the Agrotechnology Unit, Taman Pertanian Universiti, UPM. The objectives of this study are to examine the effect of different light intensities on growth of basil grown in soilless culture and to determine the optimum light intensity for high quality production of basil. Seedlings were grown in polybags (size 45cm x 20cm) consisted of coconut coir dust. Treatments consisted of three light regimes: 100, 50 and 30 % sunlight and were arranged in a Complete Randomized Block Design (RCBD) with six replications. The parameters include plant height and total leaf area was collected every week. Root and shoot fresh and dry weight, root shoot ratio, days to flowering, relative chlorophyll content, net photosynthesis, stomata conductance and nutrient analysis data were collected at week five. All data were analyzed by Analysis ofYariance (ANOYA) using Statistical Analysis System (SAS) and means of separation were determined by Tukey's Studentized Range (HSD) test. Results show that, lower light intensity reduced shoot and root fresh weight, shoot and root dry weight, root shoot ratio, relative chlorophyll content, stomata conductance and amount for N, P, K. The net photosynthesis was highest at 100% sunlight. Plant height and leaf area significantly were different. Days to flowering increased as the light intensity decreased. In conclusion, basil grown under 100% sunlight, performed and gave the best quality development.